Allodynia and Descending Pain Modulation in Migraine: A Resting State Functional Connectivity Analysis. Issue 1 (25th October 2013) - Schwedt, Todd J.; Larson‐Prior, Linda; Coalson, Rebecca S.; Nolan, Tracy; Mar, Soe; Ances, Beau M.; Benzinger, Tammie; Schlaggar, Bradley L.
Abstract Objective Most migraineurs develop cutaneous allodynia during migraines, and many have cutaneous sensitization between attacks. Atypical pain modulation via the descending pain system may contribute to this sensitization and allodynia. The objective of this study was to test the hypothesis that compared with non‐allodynic migraineurs, allodynic migraineurs have atypical periaqueductal gray (PAG) and nucleus cuneiformis (NCF) resting‐state functional connectivity (rs‐fc) with other pain processing regions. Design Ten minutes resting‐state blood‐oxygen‐level‐dependent data were collected from 38 adult migraineurs and 20 controls. Seed‐based analyses compared whole‐brain rs‐fc with PAG and with NCF in migraineurs with severe ictal allodynia (N = 8) to migraineurs with no ictal allodynia (N = 8). Correlations between the strength of functional connections that differed between severely allodynic and non‐allodynic migraineurs with allodynia severity were determined for all migraineurs (N = 38). PAG and NCF rs‐fc in all migraineurs was compared with rs‐fc in controls. Results Migraineurs with severe allodynia had stronger PAG and NCF rs‐fc to other brainstem, thalamic, insula and cerebellar regions that participate in discriminative pain processing, as well as to frontal and temporal regions implicated in higher order pain modulation. Evidence that these rs‐fc differences were specific for allodynia included: 1) strong correlations between some rs‐fc strengths and allodynia severity among all migraineurs; and 2) absence of overlap when comparing rs‐fc differences in severely allodynic vs non‐allodynic migraineurs with those in all migraineurs vs controls. Conclusion Atypical rs‐fc of brainstem descending modulatory pain regions with other brainstem and higher order pain‐modulating regions is associated with migraine‐related allodynia.